Polyether-modified siloxane stabilized dispersion system on the physical stability and control release of double (W/O/W) emulsions. (1st December 2020) - Lin, Chao; Debeli, Dereje Kebebew; Gan, Liang; Deng, Jianjun; Hu, Liuyun; Shan, Guorong
Highlights: Different PMS and SC polymers were applied to formulate W/O/W emulsions. The stabilities and controlled releases of Mg 2+ from W/O/W emulsions were affected by MW of PMS. The PMS double emulsions have 15–20 days of storage stabilities. Abstract: In this work, three different polyether-modified siloxanes (PMS1, PMS2, and PMS3) were applied to stabilize water-in-oil emulsions, and sodium caseinate (SC) was used to establish water-in-oil-in-water (W/O/W) emulsions. Here, PMS polymers were modified by Isolan GPS and SC by Tween 80. The impact of modifications on the physical stability and controlled release of W/O/W emulsions were investigated. It was found that the storage stability and control release of double emulsions were dependent on the types of PMS used, percent of Isolan GPS, and Tween 80. When PMS1 and PMS2 were combined with low percent of Isolan GPS and Tween 80, the dispersed droplet sizes were reduced, lower percent in the gravitational sedimentation were achieved than using PMS3 emulsions. The controlled releases of Mg 2+ from W/O/W emulsions by using PMS3 were slower than using other PMS. PMS3 had a strong influence in controlling the release of Mg 2+ from the double emulsions.